The influence of hamlet protein 300 and fish meal on nursery pig performance - W Ying; Joel M DeRouchey; Robert D Goodband; Michael D Tokach; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2010)
A total of 360 nursery pigs (PIC 1050 barrows) were used in a 24-d study to evaluate the effects on growth performance of nursery diets containing Hamlet Protein 300 (HP 300) or fish meal. Pigs were weaned at approximately 21 d of age and placed on a pretest diet for 7 d before dietary treatments began. Pens of pigs were balanced by initial weight and randomly allotted to 1 of 7 dietary treatments with 9 replications per treatment. The 7 dietary treatments included a control diet containing no specialty protein sources or the control diet with 2, 4 or 6% select menhaden fish meal; or the control diet with 2, 4, or 6% HP 300. All experimental diets were fed for 14 d, followed by a common diet for 10 d. Neither fish meal nor HP 300 influenced any growth performance criteria (P>0.13) from d 0 to 14. During the common period (d 14 to 24), pigs previously fed fish meal tended to have better F/G than pigs previously fed HP 300 (P = 0.09). Overall (d 0 to 24), there were no differences in growth performance between treatments (P>0.34). In conclusion, HP 300 and fish meal had similar effects on growth performance, but neither provided a benefit compared to the pigs fed the control diet.; Swine Day, Manhattan, KS, November 18, 2010
Keywords: Swine Day; 2010; Kansas Agricultural Experiment Station contribution; no. 11-016-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1038; Swine; Fish meal; Hamlet Protein 300; Nursery pig